Evaluating Trust in the Patient–Dentist Relationship: A Mixed-Method Study. (July 2023) - Tiwari, T.; Maliq, N.N.; Rai, N.; Holtzmann, J.; Yates, L.; Diep, V.; Tranby, E.P.; Frantsve-Hawley, J.
Background: The objective of this article was to understand the trust of study participants in dental providers and trust-building practices used by dentists to establish and maintain trust with their patients. Methods: This study used a concurrent cross-sectional mixed-methods design to measure the participants' trust in their dental providers. An 11-item Dental Trust Scale (DTS) questionnaire was administered to 150 White, Black, and Hispanic study participants. In addition, the research team conducted semistructured interviews with 7 dentists in order to understand their perspectives related to patient trust. The internal consistency of the DTS was tested using Cronbach's α. Univariate and multivariable logistic regression models were run to test the association between the DTS mean score and individual participant factors. Qualitative information from interviews was analyzed using a thematic analysis approach. Results: The overall mean score of dental trust for the entire sample was 3.4. The DTS had good internal consistency (α = 0.93). Overall, dental trust was significantly higher in participants who had a regular dentist (F = 8.74, P = 0.003). The qualitative data were grouped under these key thematic categories: the importance of trust, building trust, and trust in treatment planning. Qualitative analysis also showed that the 2 main trust-building tools used by dentists were communication and understanding the patient's lifestyle or social determinants of health. Knowledge Transfer Statement: This study provides insight into the dentist–patient relationship. It increases our understanding of levels of dental trust among patients and examines methods used by the dentist to build trust. The outcomes of this study can be considered by dentists in their everyday practice as they seek to build trust with their patients.